Inoffensivity of imupurin in pregnancy - Ina Pogonea (The Moldovan Medical Journal, 2019)
Background: Determination of imupurin inoffensivity on embryogenesis, organogenesis and teratogenesis in rats. Material and methods: The study of immupurin’s safety during pregnancy was performed on 60 rats, divided into 4 groups. Animals from the control group were given 2 ml of physiological solution (NaCl, 0.9%), and those from the experimental groups – 2 ml of imupurin suspension, internally, 1000 mg / kg in different periods of pregnancy, to investigate embryotoxic, teratogenic and fetotoxic effect. The fetuses were monitored during the postnatal period, from birth to the age of 2 months, with appreciation of the physical development, the behavior and coordination of newborn movements, the evolution of body mass in dynamics, the teeth eruption, the appearance of the hair cover, the opening of the eyes, the ability to feed individually after removal from the female. Results: The studies have shown that the pre-implantation and post-implantation indices in the control group were 4.1 and 3.8 respectively, and in experimental groups were 4.4 and 3.3. The number of live fetuses in the investigated groups was 12.1±1.5, which did not differ from the control group, whose live fetuses were 12.3±1.9. Postnatal period indices (teeth eruption, hair cover, and eye opening) were similar in all investigated groups and corresponded to the age of the rats. Conclusions: Imupurin has been shown to have no embryotoxic, fetotoxic and negative effects on the postnatal period and may be recommended in pathologies accompanying pregnancy.